Does better physical accessibility lead to higher sales revenues? - Kukanja, Marko (Academica turistica, 2023)
Despite the significance of accessibility for sustainable tourism development, littleis known about the relationship between physical accessibility and restaurant salesrevenues.Previous studies also did not consider restaurant managers’ perceptions of accessibility, although they are responsible for implementing an accessible offer. The objectives of the present study are(1) to investigate if managers of small and medium-sized restaurant enterprises (smes) perceive restaurants as physically accessible and (2) to determine if better physical accessibility generates higher sales revenues. This study was performed in two steps. First, research on accessibility and relevant leg-islation was analysed. Second, primary data was collected using a self-administered questionnaire in field research from 149 restaurant managers, and secondary finan-cial data for each sme was obtained through publicly available financial reports. To express the perspectives of people with disabilities (pwds), disability organisation representatives were included in the questionnaire development process. Descriptive statistics and correlation analyses were used to analyse the data. Findings reveal that managers have low knowledge of accessibility, perceive restaurants as relatively poorly accessible, and that physical accessibility is not correlated to sales revenues.Concerning the different layout areas,managers identified toilet facilities as the most inaccessible restaurant area. Besides the legislative responsibility, managers should also be aware of the economic potential of the disability market in tourism and thef act that an accessible offer facilitates the use of restaurants for society as a whole.The article ends with providing recommendations for the restaurant industry, policy makers, and academia.
Keywords: disability; dohodki od prodaje; fizična dostopnost; gostinstvo; invalidi; mala podjetja; managers; physical accessibility; restaurants; sales revenue; Slovenija; SMEs